Pelatihan dan Bimbingan Digital Marketing Bagi Pelaku UMKM di Kelurahan Kepanjen Lor Kota Blitar - Nabigus Thoriq Harasta; Sugito Sugito (Lembaga Pengembangan Kinerja Dosen, 2023)
Food is a basic human need, therefore, the food industry is an industry that will always grow, at least following population growth. It is not surprising that the food industry, especially small-scale industries, has sprung up to meet this demand. As a form of community service, the East Java UPN